Fair Trade Coffee : The Prospects and Pitfalls of Market-Driven Social Justice - Fridell, Gavin (Studies in Comparative Political Economy and Public Policy, 2016)
Over the past two decades, sales of fair trade coffee have grown significantly and the fair trade network has emerged as an important international development project. Activists and commentators have been quick to celebrate this sales growth, which has allowed socially just trade, labour, and environmental standards and practices to be extended to hundreds of thousands of small farmers and poor rural workers throughout the Global South. While recent assessments of the fair trade network have focused on its impact on local poverty alleviation, however, the broader political-economic and historically rooted structures that frame it have been left largely unexamined.In this study, Gavin Fridell argues that while local level analysis is important, examination of the impacts of broader structures on fair trade coffee networks, and vice versa, are of equal if not greater significance in determining their long-term developmental potential. Using case studies from Mexico and Canada, Fridell examines the fair trade coffee movement at both the global and local level, assessing its effectiveness and locating it within political and development theory. In addition, Fridell provides in-depth historical analysis of fair trade coffee in the context of global trade, and compares it with a variety of postwar development projects within the coffee industry.Timely, meticulously researched, and engagingly written, this study challenges many commonly held assumptions about the long-term prospects and pitfalls of the fair trade network's market-driven strategy in the era of globalization.